2007
DOI: 10.1039/b700163k
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vacuum filter sock surface sample collection method for Bacillus spores from porous and non-porous surfaces

Abstract: Vacuum filter socks were evaluated for recovery efficiency of powdered Bacillus atrophaeus spores from two non-porous surfaces, stainless steel and painted wallboard and two porous surfaces, carpet and bare concrete. Two surface coupons were positioned side-by-side and seeded with aerosolized Bacillus atrophaeus spores. One of the surfaces, a stainless steel reference coupon, was sized to fit into a sample vial for direct spore removal, while the other surface, a sample surface coupon, was sized for a vacuum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 13 publications
4
58
1
Order By: Relevance
“…The spore surface concentrations are controlled by varying settling time and the initial aerosolized spore concentration in the chamber. Brown et al (4)(5)(6) tested various methods of collecting samples of Bacillus subtilis spores on porous and nonporous surfaces using this approach. In these studies, surface spore concentrations of 10 2 to 10 5 CFU/cm 2 were achieved.…”
mentioning
confidence: 99%
“…The spore surface concentrations are controlled by varying settling time and the initial aerosolized spore concentration in the chamber. Brown et al (4)(5)(6) tested various methods of collecting samples of Bacillus subtilis spores on porous and nonporous surfaces using this approach. In these studies, surface spore concentrations of 10 2 to 10 5 CFU/cm 2 were achieved.…”
mentioning
confidence: 99%
“…76 (Brown et al, 2007b ;Brown et al, 2007a Another aerosol generator is the flow-focusing aerosol generator (FFAG), which is used to generate particles larger than 10 μm. This instrument relies on the formation of a stable microjet which disintegrates at a defined distance from a critical orifice.…”
Section: Aerosol Generation Methodsmentioning
confidence: 99%
“…The tested deposition with aluminum oxide particles, monodisperse polystyrene spheres, and oleic acid droplets; however, they ultimately concluded that biological particle tests are needed due to the additional complications they add to the tests. Brown et al, aerosolized BG spores into a chamber and produced surface concentrations in the range of 10 2 to 10 5 colony forming units per square centimeter for the purposes of swipe sampling (Brown et al, 2007a(Brown et al, , 2007b(Brown et al, , 2007c. The chamber included a cylinder mixing chamber, constructed from carbon steel with enamel-coated surface, and a diameter of 45 cm, a height of 30 cm, and a total volume of 0.048 m 3 .…”
Section: Aerosol Test Chambersmentioning
confidence: 99%
“…Further, because of the variability produced by having to deal with live organisms, it is not likely that the accuracy in measurement for spores will meet the NIOSH criteria. In studies of spore recovery from surfaces, the variability of CFUs per sample is not usually reported, only the recovery efficiency and its variability (Rose et al 2004;Hodges et al 2006;Brown et al 2007a;2007b;2007c). Recovery efficiency values reported in the Brown et al studies had a range of 28-90%; .…”
Section: Introductionmentioning
confidence: 99%
“…The spores were allowed to settle onto flooring material placed on a bench. Brown et al (2007a;2007b;2007c) spores into a chamber and produced surface concentrations in the range of 10 2 to 10 5 colony forming units per cm 2 . In the anthrax attack of 2001, some of the material was believed to be in a "fluidized" form (defined here as having fumed silica added).…”
Section: Introductionmentioning
confidence: 99%